2003
DOI: 10.4319/lo.2003.48.1.0068
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic paleolimnology of Lake Kinneret

Abstract: The carbonate, organic C, and N contents and their respective ␦ 13 C were measured in four cores from Lake Kinneret, Israel. Using these data and the isotopic difference between coexisting carbonate and organic C, ⌬␦ 13 C, we attempted to reconstruct the lake's productivity and regional climatic conditions during the late Holocene. The sedimentary record of the last 120 yr (for which climatological data are available) demonstrates that during periods of intense productivity, organic C content and its ␦ 13 C or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…Acetate concentrations in the sediment are 3-5% (Nü sslein et al 2001). Dubowski et al (2003) showed that the C : N value ranged between 10 and 14 in the sediments.…”
Section: Methodsmentioning
confidence: 99%
“…Acetate concentrations in the sediment are 3-5% (Nü sslein et al 2001). Dubowski et al (2003) showed that the C : N value ranged between 10 and 14 in the sediments.…”
Section: Methodsmentioning
confidence: 99%
“…The compiled sediment trap data from 1990 to 1995 also exhibited no δ 13 C alteration with trap depths (data not shown). The notion of lack of δ 13 C-POM alteration is widely accepted (Meyers 1994); it enables the application of δ 13 C-POM from sediment cores to reconstruct past environmental conditions (Brenner et al 1999, Dubowski et al 2003. The lack of alteration in isotopic composition is validated in turn by the little to no carbon isotopic fractionation when organic matter is consumed (DeNiro and Epstein 1978), which would leave the remaining organic matter intact in terms of its δ 13 C. To explore the possible causes for the significantly higher spring δ 13 C peaks in Peridinium years than in nonPeridinium years (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The freeze-dried material was subsampled to obtain both organic (POM traps ) and inorganic (mostly CaCO 3 ) material separately. The organic subsample was treated with 1 N HCl to remove CaCO 3 , dried in the hood to remove the excess acid, and stored at room temperature in a desiccator until δ 13 C analysis was performed (Dubowski et al 2003). The inorganic subsample was treated with diluted (1:5) NaOCl for 24 h to oxidize the organic matter.…”
Section: Zooplanktonmentioning
confidence: 99%
“…Circles denote shallow lakes, including Lake Wuliangsu (this study), and lakes from the Songnen Plain (Ou & Zhang, 2009), the Kajemarum Oasis (Holmes et al, 1997), and the Christmas Island (Trichet et al, 2001). Squares denote large and deep lakes, including Lakes Erie , Ontario , Mendota (Hollander et al, 1992), Qinghai (Xu et al, 2006), Pyramid (Meyers et al, 1998;Tenzer et al, 1997), Kivu (Botz et al, 1988), and Kinneret (Dubowski et al, 2003). Squares denote large and deep lakes, including Lakes Erie , Ontario , Mendota (Hollander et al, 1992), Qinghai (Xu et al, 2006), Pyramid (Meyers et al, 1998;Tenzer et al, 1997), Kivu (Botz et al, 1988), and Kinneret (Dubowski et al, 2003).…”
Section: Recycled Oc Contribution To Carbonate In Lakes Globallymentioning
confidence: 95%